Evaluation of the applications of traditional and complementary medicine in the perspective of family medicine in a tertiary referral center - Mehmet Kayhan; Erdal Dilekci (Medicine Science, 2020)
To evaluate the clinical and demographic characteristics of the patients who apply to Traditional and Complementary Medicine (TCM) center. The medical charts of patients, who were admitted to AIBU Izzet Baysal Physical Therapy and Rehabilitation Training and Research Hospital, TCM centre, from September 2018 to August 2019, were retrospectively reviewed. Only patients over the age of 18 were included in the study. 879 (84.4%) of the patients were female, 163 of them were (15.6%) male. 44 (4.2%) patients in the 18 - 24 age group, 137 (13.1%) patients in the 25 - 34 age group, 223 (21.4%) people in the 35 - 44 age group, 287 (27.5%) patients in the 45 - 54 age group, 205 (19.7%) patients were in the 55-64 age group, and 146 (14.0%) patients were in the age group 65 and over. Mean age of the patients was 48.64 ± 13.86 (19-87). 365 (35.0%) of TCM applications were made in spring, 266 (25.5%) in winter, 223 (21.5%) in summer and 188 (18.0%) in autumn. In this study, the most preferred TCM applications are acupuncture (48.1%), ozone therapy (34.3%) and mug treatment (13%), respectively. Determining by whom, in which age group and in which period of the year are more preferred TCM applications, which have been increasingly used in recent years, may prevent problems that may develop during the service delivery process. [Med-Science 2020; 9(1.000): 216-20]